Die Zukunft des Welthandels - Holger Görg; Martin Klein; Michael Pflüger; Oliver Krebs; Christoph Scherrer (Wirtschaftsdienst, 2015)
Der Welthandel ist seit den 1950er Jahren fast regelmäßig schneller gewachsen als die globale Wirtschaftsleistung. China ist inzwischen zum Exportweltmeister aufgestiegen. Möglich wurde dies durch kontinuierliche multilaterale Handelsliberalisierungen, die allerdings seit Beginn dieses Jahrhunderts stocken. Derzeit dominieren regionale Abkommen die globale Handelspolitik. Die Abkehr vom Multilateralismus ist auch als Hinwendung zu einem machtbasierten System zu verstehen. Die Interessen der schwächeren Handelsnationen werden dabei weniger berücksichtigt. Mit dem Handel wächst zudem das Verkehrsaufkommen, was ökologisch unerwünschte Folgen mit sich bringt. – – Since the 1950s, world trade has grown much faster than global economic production. Meanwhile, China has surpassed Germany as the leading export nation. Continuing trade liberalisation on a multilateral level has made this increasing global integration possible. Regional initiatives, such as the Transatlantic Trade and Investment Partnership and the Trans-Pacifi c Partnership, have attained dominance in the world trading system in recent years. Some of the well-known weaknesses of regionalism are already cropping up in the formation of these 'megaregionals'. These problems and the current challenges posed to the world trading system require a strengthening of the WTO's multilateral system. But the current bilateral and regional trade negotiations (TTIP, TPP, TiSA, etc.) aim at strengthening the already powerful, i.e. investors and transnational corporations, and they limit developing countries' possibilities for catching up. Great hopes have been invested internationalisation as a driver of innovation in Europe. If this means ever-increasing trade orientation, then these hopes are probably misplaced. The continuing expansion of world trade has ecological, social and political limits. New solutions will have to be found to hold on to the benefi ts of internationalisation in the context of stagnating or even shrinking international trade.
Keywords: F13; F18; F21; 330; Internationale Handelspolitik; Internationale Wirtschaftsbeziehungen; Weltwirtschaftsordnung; Welt